Signifikansi Maqashid asy-Syari Dalam Pemikiran asy-Syatibi Tentang Ijtihad - Samsidah Samsidar (Syariah: Jurnal Hukum dan Pemikiran, 2013)
Article try to study about ijtihad as a source of law and decision method and its relationwith maqashid asy-syari that was expanded by asy-Syatibi. Flexibilitas ijtihad can be a solution tosolve a problem in the modern society and as a basic of islamic law reform.